Exploring the Metabolic and Transcriptomic Profiles of Tetrastigma hemsleyanum for Tissue-Specific Compound Accumulation - Peng, Lingxia; Li, Hongju; Yang, Lijun; Liang, Zongsuo; Zhang, Xiaodan (Frontiers in Plant Science, 2025)
IntroductionTetrastigma hemsleyanum Diels et Gilg is a medicinal plant known for its diverse pharmacological effects, including anti-inflammatory, anti-tumor, anti-hepatocellular carcinoma, and antipyretic activities. To explore the medicinal components from different parts of the plant and to fully utilize T. hemsleyanum, this study investigated the mechanisms underlying the differential accumulation of metabolites in its tuberous roots, fibrous roots, and leaves.MethodsThis study employed a combination of metabolomics and transcriptomics to analyze the metabolic profiles of T. hemsleyanum. Using LC-MS/MS technology in positive ion mode, metabolites were identified and quantified in the tuberous roots, fibrous roots, and leaves. Key metabolic pathways were analyzed to understand the spatial distribution of bioactive compounds.ResultsA total of 65 metabolites were identified in the tuberous roots, 203 in the fibrous roots, and 235 in the leaves. The main compounds identified included flavonoids, alkaloids, terpenoids, glycosides, ketones, and amino acids and their derivatives. Flavonoids, glycosides, alkaloids, and terpenoids were strongly accumulated in the tuberous roots, while flavonoid alcohols, glycosides, alkaloids, and terpenoids were predominant in the leaves and fibrous roots. The phenylpropanoid biosynthesis pathway and isoflavonoid biosynthesis were found to play a major role in the pharmacological effects of T. hemsleyanum. The glucosinolate pathway and ABC transporters were also identified as key contributors to tissue-specific metabolic accumulation.DiscussionThese results elucidate the molecular mechanisms behind the differential accumulation of metabolites in different parts of T. hemsleyanum. The findings provide important insights into the spatial distribution of its bioactive components and their biosynthetic pathways, offering a foundation for further development and utilization of this medicinal plant.